Soybean oversowing with Urochloa brizantha and Panicum maximum and the straw formation in a no-tillage system - Correia, Núbia Maria; Gomes, Leonardo José Petean [UNESP] (Universidade Estadual de Londrina, 2016)
The objective of this study was to evaluate the soybean oversowing with braquiarão (Urochloa brizantha cv. Marandu) and colonião (Panicum maximum cv. Aruana) and the capacity of these forage crops to produce dry mass during the fall-winter-spring period. Two experiments, one for each forage species, were conducted in field conditions in the 2011/2012 season and were repeated in 2012/2013. The experimental set-up was arranged in a randomized block design with four repetitions in a 2 × 5 factorial. The soybean oversowing was studied in the development stages R6 and R8 (2011/2012) or R5 and R8 (2012/2013) with braquiarão or colonião grass in five seed amounts (200, 400, 600, 800 and 1000 points of cultural value-PCV = seeds amount x culture value). In both seasons, the braquiarão oversowing at soybean stages R5 and R6 resulted in higher dry mass production, when compared to stage R8. Additionally, the amount of 600 seeds PCV was sufficient to obtain an excellent percentage of soil cover (>95%), in addition to the satisfactory number of plants per m2 and the dry mass production. On the other hand, independent of the soybean development stage in the oversowing moment, colonião was not promising for use in this sowing type because its low stand and irregular soil covering, even at the higher seed amounts.
Keywords: Agriculture-cattle activity integration; Glycine max L. Forage grasses